A Zonal Migration of Monsoon Moisture Flux Convergence and the Strength of Madden‐Julian Oscillation Events - Samson Hagos; Chidong Zhang; L. Ruby Leung; Casey D. Burleyson; Karthik Balaguru (Geophysical Research Letters)
Abstract Understanding the variations in the strength of Madden‐Julian Oscillation (MJO) events as they propagate across the Indo‐Pacific Maritime Continent has been an unmet challenge. Moisture flux convergence estimated directly from precipitation shows a slow eastward migration of zonal moisture flux convergence between the Asian and Australian monsoon convergence centers from summer to winter. Strengths of individual MJO events vary as they propagate across this zonally and seasonally varying monsoonal moisture convergence. MJO events starting in February–April tend to be weak over the eastern Indian Ocean, but they strengthen as they propagate into the moisture convergence region over the western Pacific. During May–July, the moisture convergence pattern is reversed and MJO events weaken as they propagate into the moisture divergence region in the western Pacific. Winter MJO events are most likely to be strong over the Maritime Continent region, particularly when the Australian monsoon is strong.